O Transtorno do Déficit de Atenção e Hiperatividade (TDAH) como sistema de classificação e estigmatização em instituições escolares de São Luís – MA - DUTRA, Suzenny Nascimento (2022)
This paper seeks to analyze from a social historical point of view whether the process of classification of Attention Deficit Hyperactivity Disorder (ADHD) contributes to the disorder being seen as a category of stigmatization within the educational context. That is, we seek to understand and explain how the disorder is recognized within school institutions and how these contribute to the process of classifying certain social actors as having the disorder. This analysis is situated in the perspective of a sociology of deviation and a sociology of institutions (totals) and, in this sense, two analytical categories are mobilized, namely stigma/ deviation of Howard Becker and "total institution" of Erving Goffman. As an empirical field we chose two schools: "New Generation", a school that offers an integral and technical model education, which is the state public school network and is located in the city center of São Luís-MA. And the school "Young Universe", located in the neighborhood of Cohatrac, also in São Luís, the municipal public school system. For the construction of the empirical data of the research were mobilized, direct observation, accompanied by semi-structured interviews with institutional actors, parents/families and students.